2015
DOI: 10.1002/spe.2387
|View full text |Cite
|
Sign up to set email alerts
|

Browserbite: cross‐browser testing via image processing

Abstract: SUMMARYCross-browser compatibility testing is concerned with identifying perceptible differences in the way a Web page is rendered across different browsers or configurations thereof. Existing automated cross-browser compatibility testing methods are generally based on document object model (DOM) analysis, or in some cases, a combination of DOM analysis with screenshot capture and image processing. DOM analysis, however, may miss incompatibilities that arise not during DOM construction but rather during render… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The number of articles in relation to each browser used in the experiments were: Mozilla Firefox (10 articles), Google Chrome (7 articles), Microsoft Internet Explorer (10 articles), and Apple Safari (4 articles). It is worth noting that in [11], the experiment was conducted with 15 distinct configurations of these browsers, by changing the OS and browser versions.…”
Section: Related Work and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of articles in relation to each browser used in the experiments were: Mozilla Firefox (10 articles), Google Chrome (7 articles), Microsoft Internet Explorer (10 articles), and Apple Safari (4 articles). It is worth noting that in [11], the experiment was conducted with 15 distinct configurations of these browsers, by changing the OS and browser versions.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…Many of the reviewed studies relied on DOM-based approaches (such as [8] which reported the use DOM elements' attributes for detecting XBIs) or Computer-vision approaches (such as [5,[9][10][11] which developed image processing algorithms for detecting XBIs). However, there were also hybrid approaches, which combined DOM-based and Computer-vision approaches (such as [4,12] which used the DOM attributes alongside screenshot comparison for detecting XBIs).…”
Section: Xbi Detection Frameworkmentioning
confidence: 99%
“…DIC applies the images, which measure deformation from micrometer to nanometer range. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] If the image has spatial and high temporal, the result could be improved by DIC. 29,30 In previous studies, cell imaging was classified through machine learning (normal cell image, drug-treated cell image, diseased cell image, and cell movement).…”
Section: Methodsmentioning
confidence: 99%
“…Web page segmentation is used in various areas of software engineering. Saar et al [5] use segmentation to test cross-browser compatibility of web pages. Their approach is based on loading the same web page in two different browsers, followed by segmenting the rendered pages in the two different browsers, and finally comparing the pairs of segments to ensure both pages have been rendered in the same fashion in both browsers.…”
Section: Background and Motivating Examplementioning
confidence: 99%